Genome‐wide SNP analysis reveals an increase in adaptive genetic variation through selective breeding of coral. Issue 12 (20th June 2020) - Quigley, Kate M.; Bay, Line K.; van Oppen, Madeleine J. H.
Abstract: Marine heat waves are increasing in magnitude, duration, and frequency as a result of climate change and are the principal global driver of mortality in reef‐building corals. Resilience‐based genetic management may increase coral heat tolerance, but it is unclear how temperature responses are regulated at the genome level and thus how corals may adapt to warming naturally or through selective breeding. Here we combine phenotypic, pedigree, and genomic marker data from colonies sourced from a warm reef on the Great Barrier Reef reproductively crossed with conspecific colonies from a cooler reef to produce combinations of warm purebreds and warm‐cool hybrid larvae and juveniles. Interpopulation breeding created significantly greater genetic diversity across the coral genome compared to breeding between populations and maintained diversity in key regions associated with heat tolerance and fitness. High‐density genome‐wide scans of single nucleotide polymorphisms (SNPs) identified alleles significantly associated with larval families reared at 27.5°C (87–2, 224 loci), including loci putatively associated with proteins involved in responses to heat stress (cell membrane formation, metabolism, and immune responses). Underlying genetics of these families explained 43% of PCoA multilocus variation in survival, growth, and bleaching responses at 27.5°C and 31°C at the juvenile stage. Genetic marker contribution to total variation in fitness traits (narrow‐sense heritability) was high for survival but not for growth and bleaching in juveniles, with heritability of these traits being higher at 31°C relative to 27.5°C. While based on only a limited number of crosses, the mechanistic understanding presented here demonstrates that allele frequencies are affected by one generation of selective breeding, key information for the assessments of genetic intervention feasibility and modelling of reef futures.